Implementing Quality Early Childhood Education: Optimizing Early Childhood Services through Collaboration with the Parent-Student Association - Diah Ayu Norma Paripurnawati; Yuli Kurniawati Sugiyo Pranoto; Edi Waluyo (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Quality Early Childhood Education (ECE) services require the involvement of various stakeholders, particularly collaboration between educational institutions and parents. However, parental involvement in the implementation of ECE services still faces several challenges, including limited time and a lack of understanding regarding the importance of participation in early childhood education. This study aims to analyze the implementation of optimizing quality ECE services through partnerships with parent associations. The research employed a qualitative approach with a case study design. The research subjects consisted of the principal, teachers, and members of the parent association committee. Data were collected through in-depth interviews, participatory observation, and documentation studies, and were analyzed using descriptive qualitative analysis techniques involving data reduction, data display, and conclusion drawing. The findings revealed that structured collaboration between ECE institutions and parent associations contributed significantly to improving the quality of learning services, strengthening children’s character development, and supporting holistic child growth and development. The collaboration was implemented through parental involvement in learning activities, parenting programs, and project-based activities. Nevertheless, the study also identified challenges related to the limited participation of some parents. Therefore, continuous persuasive and educational approaches are needed to strengthen the synergy between families and schools in creating participatory, contextual, and sustainable ECE services.